Theoretical substantiation of the methodology of technical and tactical training of qualified freestyle wrestlers - Norden, A.; Kozhanov, V.; Moskovsky, A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to theoretically substantiate the methodology of technical and tactical training of qualified freestyle wrestlers.